JEJAK SAKURA DI NUSANTARA: PASANG SURUT HUBUNGAN JEPANG-INDONESIA TAHUN 1880an–1974 - Aditia Muara Padiatra (Unit Penelitian dan Publikasi Fakultas Ilmu Budaya Universitas Gadjah Mada, 2020)
As a sovereign Country, Indonesia and Japan have a long history of relations. The relationship itself is runs dynamically and based on a variety of factors, which are then interesting to study further. This cannot be avoided, because dynamics relations between Japan and Indonesia are important stories that shaping the nation history. Starting from the concept of south expansion and ends because of foreign investment, this relationship had experienced up and down from time to time. It is interesting to be able to see how the journey of the dynamics of the relationship occurs and what factors are behind it. All of this will be written through a historical perspective in order to create a common thread from the series of events that have occurred.